Comparison of phytochemicals, antioxidant and anti-inflammatory properties of sun-, oven- and freeze-dried ginger extracts - Mustafa, Iswaibah; Chin, Nyuk Ling; Fakurazi, Sharida; Palanisamy, Arulselvan (MDPI, 2019)
The effects of different drying methods, including sun-, oven-, and freeze-drying on the changes in the antioxidant and anti-inflammatory activities of ginger (Zingiber officinale var. Rubra) rhizome were studied. Sun-, oven-, and freeze-dried ginger showed a significant (p < 0.05) increase in phenolic content by 1.79, 1.53, and 1.91-fold; flavonoid content increased by 6.06, 5.27, and 4.90-fold; FRAP increased by 3.95, 3.51, and 3.15-fold; ABTS•+ scavenging activity increased by 2.07, 1.72, and 1.61-fold; and DPPH• inhibition increased by 78%, 58%, and 56%, respectively. Dried ginger also exhibited better inhibitory effects on the lipopolysaccharides-induced nitric oxide production in murine macrophage RAW 264.7. The drying process demonstrated a positive effect on the bioactivities of ginger. The sun-dried ginger exhibited the most potent antioxidant properties with the best enhanced anti-inflammatory activity followed by the oven-dried ginger and lastly, the freeze-dried ginger.